Facile synthesis of polypyrrole nanofiber and its enhanced electrochemical performances in different electrolytes - C. K. Das; S. Sahoo; S. Dhibar (eXPRESS Polymer Letters, 2012)
A porous nanocomposite based on polypyrrole (PPy) and sodium alginate (SA) has been synthesized by easy, inexpensive, eco-friendly method. As prepared nanocomposite showed fibrillar morphology in transmission electron microscopic (TEM) analysis. The average diameter of ~100 nm for the nanofibers was observed from scanning electron microscopic (SEM) analysis. As prepared nanofiber, was investigated as an electrode material for supercapacitor application in different aqueous electrolyte solutions. PPy nanofiber showed enhanced electrochemical performances in 1M KCl solution as compared to 1M Na2SO4 solution. Maximum specific capacitance of 284 F/g was found for this composite in 1 M KCl electrolyte. It showed 76% specific capacitance retention after 600 cycles in 1 M KCl solution. Electrochemical Impedance Spectra showed moderate capacitive behavior of the composite in both the electrolytes. Further PPy nanofiber demonstrated higher thermal stability as compared to pure PPy.